From little acorns..: environmental action as a source of well-being for schoolchildren. (2nd January 2016) - Waite, S.; Goodenough, A.; Norris, V.; Puttick, N.
Abstract: Pastoral care in education may take many forms but increasing emphasis on education for sustainable development (ESD) and concern about children's disconnection from nature suggests that our understanding of care should perhaps encompass the more than human world. The study described in this article examines longer term perspectives on well-being and looks at the possible benefits of environmental action for happiness and positive functioning. Considering the role of memory in the reconstruction of a past experience of tree planting, we suggest that well-being is constantly being reframed within the flux of life course and education. From survey responses and subsequent discussion groups in secondary schools exploring such memories, a deeper understanding of what well-being and connectedness to nature mean to young people within this case study is achieved. We note interdependencies between personal and planetary well-being within respondents' reflections and consider whether experiences of environmental action and its positioning as an act of altruism for the greater good might provide a source of positive feelings for young people not only at the time, but through subsequent recollection.